FAMILY COHESION, INTERPERSONAL COMMUNICATION, AND SMARTPHONE ADDICTION: DOES IT AFFECT CHILDREN’S EMOTIONAL DYSREGULATION? - Irfan Fauzi Rachmat; Sofia Hartati; Erdawati Erdawati (Jurnal Cakrawala Pendidikan, 2021)
Emotional dysregulation in early childhood has shown various early symptoms, such as aggressiveness, anxiety, short attention span, etc. This study aims to determine the effects of family cohesion, interpersonal communication, and smartphone addiction variables on children's emotional dysregulation. The respondents of this study were 338 students’ parents from Cirebon City, Indonesia. Data were collected by means of online questionnaires distributed individually to each kindergarten selected using proportionate cluster random sampling. The results of this study show that two variables, namely family cohesion (p = .031) and interpersonal communication (p = .016) have negative direct effects on children's emotional dysregulation. Meanwhile, smartphone addiction (p = .000) directly affects children's emotional dysregulation. From the results, it is assumed that children's emotional dysregulation will decrease when there is a focus on improving the quality of family cohesion and on decreasing the level of smartphone addiction. Besides, the government, schools, and parents should concern about and implement a policy to keep on monitoring children when using smartphones and developing positive and harmonious family cohesion.